2022
DOI: 10.1088/1361-6463/ac8d15
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional porous tungsten via DLP 3D printing from transparent ink

Abstract: Tungsten, an essential refractory metal material, has the characteristics of high melting and boiling points, high hardness, low expansion coefficient, and low vapor pressure. An indirect strategy to print three-dimensional (3D) refractory metal materials via digital light processing (DLP) followed by a post-treatment process was proposed. To analyze this strategy, a transparent ink with tungsten salts was developed, printed into a 3D precursor via DLP, and subsequently transited into 3D porous tungsten. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…S1, and table S1) (23,24). A phase elimination strategy, which involves the selective removal of the sacrificial component in the ink (25)(26)(27)(28), was used to transform as-printed 3D filaments into porous architectures to enhance the performance. This technology enables low-cost customizable prototyping of sustainable and wearable multifunctional physiochemical sensing systems via a simple process, ideally suitable for remote healthcare surveillance (fig.…”
Section: Introductionmentioning
confidence: 99%
“…S1, and table S1) (23,24). A phase elimination strategy, which involves the selective removal of the sacrificial component in the ink (25)(26)(27)(28), was used to transform as-printed 3D filaments into porous architectures to enhance the performance. This technology enables low-cost customizable prototyping of sustainable and wearable multifunctional physiochemical sensing systems via a simple process, ideally suitable for remote healthcare surveillance (fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that digital light processing (DLP) was utilized to structure tungsten oxidebased catalysts, tungsten, and a tungsten nickel alloy. [47][48][49] In the former two applications, an ammonium metatungstate containing aqueous ink was structured, then dried for 3-4 days at room temperature, and subsequently thermally reduced to tungsten oxide and porous tungsten, respectively. [47,48] The resulting tungsten oxide was successfully utilized as a catalyst for the hydrogenation of alkynes and nitrobenzenes, whereas the resulting porous tungsten reached feature sizes of around 700 μm.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] In the former two applications, an ammonium metatungstate containing aqueous ink was structured, then dried for 3-4 days at room temperature, and subsequently thermally reduced to tungsten oxide and porous tungsten, respectively. [47,48] The resulting tungsten oxide was successfully utilized as a catalyst for the hydrogenation of alkynes and nitrobenzenes, whereas the resulting porous tungsten reached feature sizes of around 700 μm. [47,48] In the latter, 3D-architected hydrogels were manufactured as scaffolds by DLP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten is a refractory metal that presents high strength and hardness, good thermal and electrical conductivity, high melting point and low thermal expansion coefficient, and good corrosion resistance. [1][2][3][4][5][6][7] Owing to these prominent properties, tungsten finds its application in many areas, such as integrated circuits, gun bullet and nuclear facility materials, fusion devices, and photoelectric materials. [4][5][6][7] In addition, due to the clear improvement of the strength, wear and corrosion resistance, tungsten is a commonly used alloying element, and tungsten carbide has been selected as a good reinforcing phase for various alloys used in aerospace and tooling industries.…”
Section: Introductionmentioning
confidence: 99%